1972
DOI: 10.1002/bit.260140111
|View full text |Cite
|
Sign up to set email alerts
|

Continuous culture of Pseudomonas fluorescens with sodium maleate as a carbon source

Abstract: Pseudomonas fluorescens (ATCC 11150) was grown in batch and continuous culture in minimal media with sodium maleate as growth-limiting sole organic carbon source. Growth was followed by turbidity and dry weight measurements. Gross composition of washed cells (relative amounts of protein, lipid, RNA, and DNA) and the distribution of amino acids in protein hydrolysates of the cells were determined for cells grown in continuous culture a t various dilution rates. Extracellular concentrations of the original carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1972
1972
1984
1984

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Fumarate, an intermediate of maleate metabolism, was found to accumulate in the extracellular phase during the batch growth of P. fluorescens on sodium maleate. 4 It was suggested that the assumption of a single rate-limiting step characterizing the overall growth of microorganisms is not a valid one in modeling the growth of this microorganism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fumarate, an intermediate of maleate metabolism, was found to accumulate in the extracellular phase during the batch growth of P. fluorescens on sodium maleate. 4 It was suggested that the assumption of a single rate-limiting step characterizing the overall growth of microorganisms is not a valid one in modeling the growth of this microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…In the ribulose monophosphate cycle methylotrophs, formaldehyde plays an important role in distributing the flow of the methanol carbon between the respiratory and assimilatory pathway^.^,'^ The complex kinetics aggravate the problem associated with the startup and stabilization of continuous bioreactors. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] An explanation of these phenomena should provide a greater understanding of microbial systems and could lead to improved product formation through changes in process control strategy. With this ultimate objective in mind a detailed investigation of the batch growth behavior of a methanol-utilizing bacterium, L3, was undertaken.…”
Section: Introductionmentioning
confidence: 99%